The World according to Gore the incredible vision of the man who should be president - Gore, Albert 1948-; Katovsky, Bill. (New York Skyhorse Pub., 2007)
A collection of quotes by former Vice President Al Gore.
CSSP-6804 donated by The Rotary Club Beaverton, Oregon, United States of America.
Keywords: Gore, Albert -- 1948- -- Quotations; Global warming -- Quotations, maxims, etc; United States -- Politics and government -- 2001-2009 -- Quotations, maxims, etc; United States -- Politics and government -- 1993-2001 -- Quotations, maxims, etc